Behaviour of gut bacteria upon stress in infants with ileostomy due to Hirschsprung disease - khan, Umama (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of M.Sc in Biotechnology, 2017.